Event Structure Semantics for CCS and Related Languages - Winskel, Glynn (DAIMI Report Series, 2002)
We give denotational semantics to a wide range of parallel programming languages based on the ideas of Milner’s CCS, that processes communicate by events of mutual synchronisation. Processes are denoted by labelled event structures. Event structures represent concurrency rather directly as in net theory. The semantics does not simulate concurrency by non-deterministic interleaving.